2021
DOI: 10.1111/nph.17365
|View full text |Cite
|
Sign up to set email alerts
|

New insight to the role of microbes in the methane exchange in trees: evidence from metagenomic sequencing

Abstract: Methane (CH 4 ) exchange in tree stems and canopies and the processes involved are among the least understood components of the global CH 4 cycle. Recent studies have focused on quantifying tree stems as sources of CH 4 and understanding abiotic CH 4 emissions in plant canopies, with the role of microbial in situ CH 4 formation receiving less attention. Moreover, despite initial reports revealing CH 4 consumption, studies have not adequately evaluated the potential of microbial CH 4 oxidation within trees. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 111 publications
2
42
0
Order By: Relevance
“…A brief summary of the CH 4 fluxes from Norway spruce shoots measured in 2020 was presented previously by Putkinen et al . (2021); however, so far, no thorough analysis of this dataset has been reported. Our data from 2019 or from the Scots pine measurements of 2020 have not been presented before.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A brief summary of the CH 4 fluxes from Norway spruce shoots measured in 2020 was presented previously by Putkinen et al . (2021); however, so far, no thorough analysis of this dataset has been reported. Our data from 2019 or from the Scots pine measurements of 2020 have not been presented before.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, there were 181 Scots pine, 53 Norway spruce and 55 empty chamber measurements made in 2019, and 205 Scots pine, 89 Norway spruce and 46 empty chamber measurements made in 2020. A brief summary of the CH 4 fluxes from Norway spruce shoots measured in 2020 was presented previously by Putkinen et al (2021); however, so far, no thorough analysis of this dataset has been reported. Our data from 2019 or from the Scots pine measurements of 2020 have not been presented before.…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Biomethane is produced solely by microbial methanogens, which belong to the archaea kingdom, yet precise microbial mechanisms of biomethane production are not fully understood [114,21]. A better knowledge of factors controlling biomethane emission would be useful both to improve industrial biomethane production, and to design techniques of land management that limit methane emission to the atmosphere [24,79,80,96]. This manuscript reviews the latest reports on mechanisms of methanogenesis by anaerobic fermentation.…”
Section: Introductionmentioning
confidence: 99%